Financial incentives and the location of tourism facilities in Greece - Irene Daskalopoulou; Anastasia Petrou; Dimitris Skuras (European Regional Science Association (ERSA), 2002)
The development of tourism activities in Greece has met a significant growth rate over the last two decades. At the same time, tourism facilities were developed in regions, which did not constitute traditional tourism destinations, thus changing the pattern of the regional allocation of tourism facilities. This occurred due to two reasons. First, the changing pattern of tourism arrivals which clearly moved out of the Greater Athens area to the Aegean and Ionian islands and Crete. Second, regional development policy provided financial incentives and assisted investments in the tourism sector of certain Greek regions. A database concerning 4,603 assisted investments realized in the tourism sector from 1982 onwards, has been assembled. The present paper examines the factors influencing the regional location of these investments. Among the factors researched are the effects of the size of financial assistance and the suitability of the region for the development of tourism facilities. Furthermore, the paper attempts to evaluate the regional policy's effects on the location of the tourism sector in Greece.
Keywords: 330